Hubungan Antara Quality of Work Life dan Stres Kerja Pada Anggota Ditreskrimsus Polda Jambi - Gibral Hamdi; Fadzlul Fadzlul; Jelpa Periantalo (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
The police institution is a law enforcement agency whose operational effectiveness heavily depends on the management of human resources to support organizational development and sustainability. The Directorate of Special Criminal Investigation (Ditreskrimsus) holds a strategic role in handling specialized and complex crimes. Its duties involve addressing various forms of criminal activity with high levels of risk and uncertainty. Such risks are often unpredictable and may arise suddenly. Continuous readiness and sustained vigilance in diverse situations can serve as significant sources of work-related stress. One strategy to mitigate work stress is by enhancing Quality of Work Life (QWL). This study aims to examine the relationship between QWL and work stress among members of the Ditreskrimsus of Polda Jambi. A quantitative approach with a correlational research design was employed, involving 115 members selected through purposive sampling. Data were collected online using questionnaires consisting of a QWL scale and a Work Stress scale. Correlation analysis conducted using SPSS indicated that the majority of respondents were in the moderate category. The findings revealed a significant negative relationship between QWL and Work Stress, with a correlation coefficient of r = -0.549 and a significance level of p < 0.001. These results underscore the importance of continuously improving various aspects of QWL as an effective strategy to prevent and reduce work-related stress.